Lessons from a co-design team on supporting student motivation in middle school science classrooms. Issue 1 (2nd January 2022) - Marchand, Gwen C.; Schmidt, Jennifer A.; Linnenbrink-Garcia, Lisa; Harris, Christopher J.; McKinney, David; Liu, Pei Pei
ABSTRACT: Decades of motivation research have yielded a set of Motivation Design Principles (MDPs) that can be leveraged to support the development of student motivation and engagement in the classroom. This article addresses the translation of these guiding principles to teacher professional learning and subsequently, classroom practice. Drawing from published literature, as well as the experiences of a co-design team of motivation and science education researchers and middle school science teachers, we address the landscape of decision points for designing and implementing professional learning focused on supporting middle school students' motivation in science. We identify 3 key decision points: (1) the extent to which professional learning should focus on general principles or specific practices; (2) the appropriate level(s) for translation of the MDPs into practice; and (3) the creation of opportunities for teacher reflection and self-assessment of their practice on student motivation and engagement.